Hypercapnic and Hypoxic Respiratory Response during Wakefulness and Sleep in a Streptozotocin Model of Alzheimer's Disease in Rats - Vicente, Mariane C. [UNESP]; Almeida, Maria C.; Bícego, Kênia C. [UNESP]; Carrettiero, Daniel C.; Gargaglioni, Luciane H. [UNESP] (SAGE Publications, 2018)
Besides the typical cognitive decline, patients with Alzheimer's disease (AD) develop disorders of the respiratory system, such as sleep apnea, shortness of breath, and arrhythmias. These symptoms are aggravated with the progression of the disease. However, the cause and nature of these disturbances are not well understood. Here, we treated animals with intracerebroventricular streptozotocin (STZ, 2 mg/kg), a drug that has been described to cause Alzheimer-like behavioral and histopathological impairments. We measured ventilation (V E), electroencephalography, and electromyography during normocapnia, hypercapnia, and hypoxia in Wistar rats. In addition, we performed western blot analyses for phosphorylated tau, total tau, and amyloid-β (Aβ) peptide in the locus coeruleus (LC), retrotrapezoid nucleus, medullary raphe, pre-Bötzinger/Bötzinger complex, and hippocampus, and evaluated memory and learning acquisition using the Barnes maze. STZ treatment promoted memory and learning deficits and increased the percentage of total wakefulness during normocapnia and hypercapnia due to a reduction in the length of episodes of wakefulness. CO2-drive to breathe during wakefulness was increased by 26 in STZ-treated rats due to an enhanced tidal volume, but no changes in V E were observed in room air or hypoxic conditions. The STZ group also showed a 70 increase of Aβ in the LC and no change in tau protein phosphorylation. In addition, no alteration in body temperature was observed. Our findings suggest that AD animals present an increased sensitivity to CO2 during wakefulness, enhanced Aβ in the LC, and sleep disruption.
Keywords: Breathing; chemosensitivity; dementia; hypoxia; locus coeruleus; streptozotocin